Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/bit.25582
|View full text |Cite
|
Sign up to set email alerts
|

Expansion, harvest and cryopreservation of human mesenchymal stem cells in a serum‐free microcarrier process

Abstract: Human mesenchymal stem cell (hMSC) therapies are currently progressing through clinical development, driving the need for consistent, and cost effective manufacturing processes to meet the lot‐sizes required for commercial production. The use of animal‐derived serum is common in hMSC culture but has many drawbacks such as limited supply, lot‐to‐lot variability, increased regulatory burden, possibility of pathogen transmission, and reduced scope for process optimization. These constraints may impact the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 35 publications
11
72
2
Order By: Relevance
“…Thus, serum free culture is a direction in the future standardized production of biological products with bioreactors [51,52]. It is necessary to investigate the metabolic characteristics of SCs in large scale expansion of cells, design the key components in the serum free medium and optimize the physical and chemical properties of the medium, which may develop individualized culture medium [53].…”
Section: Nutrient Supply and Metabolismmentioning
confidence: 99%
“…Thus, serum free culture is a direction in the future standardized production of biological products with bioreactors [51,52]. It is necessary to investigate the metabolic characteristics of SCs in large scale expansion of cells, design the key components in the serum free medium and optimize the physical and chemical properties of the medium, which may develop individualized culture medium [53].…”
Section: Nutrient Supply and Metabolismmentioning
confidence: 99%
“…However for many clinical indications, achieving lot sizes of several hundred billion to trillions of cells will be imperative for commercial success; utilizing high-density bioreactor manufacturing platforms, such as stirred-tank bioreactors in conjunction with microcarriers, is likely to be the only way to accomplish this [21][22][23][24][25].…”
Section: Existing Manufac-turing and Distribution Solutionsmentioning
confidence: 99%
“…The cell density achieved was ~ 1.7 x 10 5 cells/mL, although recent studies by the group and others have demonstrated cell densities approaching clinically-relevant numbers of ~ 1 x 10 6 cells/mL [15,16]. It is likely with further bioprocess development and parameter optimisation, cell densities will continue to increase, as has been the case with traditional biopharmaceutical development.…”
mentioning
confidence: 97%